BEYOND THE OPERATION THEATRE: OUR EXPERIENCE IN COVID-19 ICU - Kaukab Majeed (Army Medical College Rawalpindi, 2020)
The COVID-19 pandemic took world by storm soon after its emergence. People living in all parts of world fell a prey to this deadly disease. It affected individuals in all walks of life in one way or the other. After declaration of Pak Emirates Military Hospital as COVID-19 specific hospital, development of four intensive care units and involvement of multiple specialties led us to new horizons of clinical care. We experienced a transition of usual medical practice.